STRATEGI KOMUNIKASI DINAS SOSIAL DALAM MENSOSIALISASIKAN PERDA NOMOR 12 TAHUN 2008 DI KOTA PEKANBARU - Ravi Oktafriansyah; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Pekanbaru city regulation number 12 in 2008, CHAPTER 3 Prohibition is a rule made by the Pekanbaru city government which regulates the prohibition of begging activities to create social order for the entire population of Pekanbaru. In addition to the prohibition for beggars, this PERDA also provides information for the people of Pekanbaru themselves so as not to provide assistance in any form to beggars. This research was carried out at the Office of the Satpol PP, the Department of Social Affairs and the Cemetery of the City of Pekanbaru. This research was conducted with the aim of : (1) To find out the Communication Strategy of the Social Service, the team chose to socialize Pekanbaru City Regulation number 12 in 2008 about social order in policing, fostering homelessness and beggars in Pekanbaru City (2) To find out the Social Service Communication Strategy in determining the target of socialization of Pekanbaru City Regional Regulation number 12 of 2008 concerning social order in order, coaching homeless people and beggars in Pekanbaru City , (3) To find out the Social Service Communication Strategy, do a socialization plan on Pekanbaru City Regulation number 12 of 2008, (4) To find out the Social Service Communication Strategy in choosing messages and communication media in socializing Pekanbaru City Regional Regulation number 12 of 2008, (5) To find out the Social Service Communication Strategy in determining the time to conduct a socialization of Pekanbaru City Regulation number 12 of 2008.2.3.1 Data collection techniques that I use in this study are observation, interview, and documentation techniques. With informants as many as one person from the social service as a PERDA implementer, one person of Pekanbaru’s public as audiences and one beggar as an actor in this policy. Then the data analysis technique that the writer uses in this research is qualitative descriptive, that is the data collected is processed and analyzed by describing and linking with the theory in accordance with the existing problems, and tabulated in accordance with the composition of the data needed to answer each problem then give an interpretation of the relevant results, then draw conclusions and suggestions.Based on the results of research conducted by the author, the Social Service Communication Strategy in socializing Regional Regulation Number 12 of 2008 concerning Social Order in the City Pekanbaru has not gone well, because there are several problems namely the lack of use of communication media to disseminate PERDA information to the community, the need for more oversight from the Social Service Office homeless and beggars who roam the city of Pekanbaru, lack of cooperation provided by the community regarding the implementation of PERDA number 12 in 2008, CHAPTER 3 prohibition in the City of Pekanbaru